The Book of Ben Sira From a Reception-Historical Perspective: Hubert Frankemölle’s Commentary on the Letter of James - Wischmeyer, Oda (Ben Sira in Conversation with Traditions. A Festschrift for Prof. Núria Calduch-Benages on the Occasion of Her 65th Birthday, 2022)
The point of departure of this article is Nuria Calduch-Benages's contribution on Sir 2:1 to the Festschrift for Alexander A. di Lella in 2005 where she pointed out the parallels between Sir 2:1 and Jas 1:2. Hubert Frankemolle, in his two-volume commentary on the Letter of James in 1994, already followed the history of the reception of the book of Ben Sira in the Letter of James and referred especially to Jas 1:2-18 and the motif of peirasmos or trial. In the present contribution, Frankemolle's interpretive approach is re-examined and by comparing texts from Ben Sira and James, a more precise determination of the Wirkungsgeschichte of Ben Sira's wisdom writing in the Letter of James is attempted.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Control of the tongue; Early imperial literature; Intertextuality; Jas 3:1-12; Reception history; Sir 28:8-26